Hubungan Pengetahuan, Sikap, Dan Tindakan Kontrol Plak Dengan Kondisi Jaringan Periodontal Pada Remaja Usia 15-19 Tahun: Studi Observasional Potong-Lintang - Andi Aulia Nur Afifah; Nuryanni Dihin Utami; Sylvia Agustin (Jurnal Skala Kesehatan, 2026)
Periodontal disease is a chronic inflammatory condition caused by plaque accumulation resulting from poor oral hygiene. Preventive measures include plaque control behaviors encompassing knowledge, attitudes, and actions through mechanical and chemical methods. This study aims to determine the relationship between knowledge, attitudes, and plaque control actions with periodontal tissue conditions in adolescents aged 15-19 years at SMA Negeri 06 Samarinda. This was an analytical observational study with a cross-sectional approach. Purposive sampling was used to recruit 97 students from SMA Negeri 06 Samarinda. Data were collected using a questionnaire to measure knowledge, attitudes, and plaque control practices, along with periodontal tissue examination using the Community Periodontal Index (CPI). Data were analyzed using Chi-Square test and Spearman correlation. Results showed the majority of respondents' behavior (36.1%) was in the moderate category. Bivariate analysis revealed significant relationships between knowledge (p=0.000; r=-0.647), attitudes (p=0.000; r=-0.686), and actions (p=0.000; r=-0.743) with periodontal tissue condition. In conclusion, there is a strong relationship between knowledge, attitudes, and plaque control actions with periodontal tissue condition in adolescents aged 15-19 years at SMA Negeri 06 Samarinda. The implication of this study is the need for comprehensive dental health education for adolescents through school-based programs.